(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Lexical transformations represent a central mechanism through which translators resolve semantic and cultural incongruities between languages. This article investigates the functional role of lexical transformations in English–Uzbek translation, focusing on addition, omission, specification, generalization, metaphoric adaptation, and antonymic restructuring. Employing a qualitative comparative approach, the study analyzes selected translation instances within established theoretical models of translation equivalence. The results indicate that lexical transformations operate as systematic strategies rather than optional adjustments, ensuring semantic accuracy, stylistic acceptability, and communicative effectiveness. The study offers an original contribution by contextualizing lexical transformation theory within the English–Uzbek language pair.